(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article deals with lingual didactic problems of the development of critical thinking skills of students at lessons on methodic Ukrainian language learning. The author proposes educational methods, which of develop the critical thinking of students-philology.